Determining Factors of Porang Farming Sustainability in North Lombok Regency - Utami , Desak Putu Indah Chandra; Tanaya, I Gusti Lanang Parta; Sukardi, Lalu (Pascasarjana, Mataram University, 2025)
The purpose of this study was to analyze the level of sustainability of porang farming based on five dimensions, including ecological, economic, social, technological and institutional dimensions and to analyze the factors that influence the sustainability of porang farming in North Lombok Regency. This study used a qualitative quantitative descriptive method with the unit of analysis being individual porang farmers in Bayan and Gangga Districts. The analysis used was the Multi Dimensional Scaling (MDS) method with Rap-PKLU using an approach modified from the RAPFISH program. Based on the results of the study, it is known that the level of sustainability of porang farming in the social dimension (81.68; sustainable), ecological dimension (74.80; quite sustainable), economic, technological and institutional dimensions (46.64; 43.47; 48.89; less sustainable). The determining factors that need to be considered to increase the index of the sustainability status of porang farming in each dimension are 1) ecological dimension: changes in land cover, porang plant care and diversity of shade plants; 2) economic dimension: diversification of income sources, stability of selling prices and economic growth; 3) social dimension: average age of farmers and land ownership status of agricultural businesses; 4) technological dimension: porang harvesting techniques, fertilization measures and post-harvest handling and 5) institutional dimension: cooperation with partners, agricultural extension workers, the existence of Microfinance Institutions (MFIs) and the intensity of group meetings